Social capital and the COVID-19 pandemic threat: The Russian experience - Tatarko, Alexander; Jurcik, Tomas; Boehnke, Klaus (Frontiers in Sociology, 2022)
Social capital is an important resource for the wellbeing of both the individual and society. Since the beginning of the COVID-19 pandemic, many studies have been conducted to explore the role of social capital in coping with the negative consequences of the pandemic. However, how the pandemic itself can affect the social capital of people has yet to be studied. Try to fill this gap, we aimed at testing the association between the individually perceived coronavirus threat and such indicators of social capital as general social trust, institutional trust, and the quality of various types of people's social relationships (with family, friends, colleagues, neighbors, residents of a locality, residents of a country). Data were collected in different regions of the Russian Federation for a convenience sample of 500 respondents. The study found that the individually perceived coronavirus threat was positively associated with institutional trust, but not with general social trust. Moreover, this covariation was moderated by age: an institutional trust-threat relation emerged only in older respondents with an average age of around 60, but not in younger participants. Furthermore, the study found that perceived coronavirus threat was associated with closer relationships in the family, but simultaneously with an increased distance in relations with neighbors and residents of the respondents' locality. In summary, the study indicated that “strong” ties (i.e., with family, colleagues, and friends) either remained unchanged or were intensified in the face of the pandemic threat, whereas “weak” ties (i.e., with neighbors, residents of the same locality, and fellow citizens) tended to weaken even more.